5. Q5g
Save videos to My Cheatsheet for later, for easy studying.
Video Solution
Q1
Q2
Q3
L1
L2
L3
Similar Question 1
<p> Fully expand and collect the like terms using short cuts.</p><p><code class='latex inline'>\displaystyle (x^2 + x + 1)(x^2 + x - 1) </code></p>
Similar Question 2
<p>Expand and simplify.</p><p><code class='latex inline'>(w-v)(w+v)</code></p>
Similar Question 3
<p>Expand and simplify.</p><p><code class='latex inline'>(8h-3f)(8h+3f)</code></p>
Similar Questions
Learning Path
L1 Quick Intro to Factoring Trinomial with Leading a
L2 Introduction to Factoring ax^2+bx+c
L3 Factoring ax^2+bx+c, ex1
Now You Try
<p> Fully expand and collect the like terms using short cuts.</p><p><code class='latex inline'>\displaystyle (x^2 + x + 1)(x^2 + x - 1) </code></p>
<p>Expand and simplify.</p><p> <code class='latex inline'>(x+12)(x-12)</code></p>
<p>Simplify </p><p><code class='latex inline'>\displaystyle (2x+y)(x-y)-(x^2+y^2) </code></p>
<p>Expand and simplify. Verify your answers. Check that substituting x = 3 into the original expression and the simplified expansion yields the same answer.</p><p><code class='latex inline'>(x+6)^2</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(a-b)(a+b)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(v+1)(v-1)</code></p>
<p> Expand the following using <code class='latex inline'>(a - b)(a + b) = a^2 - b^2</code> short cut.</p><p><code class='latex inline'> \begin{array}{cccc} &(a)& (x - 2)(x + 2) &(b)& (x + 9)(x - 9) & (c)& (x - \frac{1}{2})(x + \frac{1}{2}) \end{array} </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(s+13)(s-13)</code></p>
<p> Fully expand and collect the like terms using short cuts.</p><p><code class='latex inline'>\displaystyle (2x^2 + x + 1)(2x^2 + x - 1) </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(2g-3h)(2g+3h)</code></p>
<p>Simplify the following.</p><p> <code class='latex inline'>\displaystyle (x - 3)(x + 4)+3(x^2 -x + 2) </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(7g-3h)(7g+3h)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(a-1)(a+1)</code></p>
<p>Expand and simplify. Verify your answers. Check that substituting x = 3 into the original expression and the simplified expansion yields the same answer.</p><p><code class='latex inline'>(x-2)(x+2)</code></p>
<p> Fully expand and collect the like terms using short cuts.</p><p><code class='latex inline'>\displaystyle (2x^2 + x - 1)(2x^2 + x + 1) </code></p>
<p>Expand and simplify. Verify your answers. Check that graphing both the original expression and the simplified expansion using a graphing calculator yields only one graph.</p><p><code class='latex inline'>(x+3)(x-3)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(y-7)(y+7)</code></p>
<p> Fully expand and collect the like terms using short cuts.</p><p><code class='latex inline'>\displaystyle (3x - 2y + 1)(3x - 2y - 1) </code></p>
<p>Expand and simplify each expression.</p><p><code class='latex inline'>\displaystyle 4(k - 1)(k + 1) </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(u-6)(u+6)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(9x-8y)(9x+8y)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(3m-n)(3m+n)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(y+6x)(y-6x)</code></p>
<p>Apply the distributive property to simplify the following. </p><p><code class='latex inline'>(x+3)(2x+4)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(8h-3f)(8h+3f)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(t+4)(t-4)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(e+5)(e-5)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'> (k + 1)(k^2 -2k -1) </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>-(4r+5s)(4r-5s)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(w-v)(w+v)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(k+11)(k-11)</code></p>
<p>Expand and simplify.</p><p> <code class='latex inline'>(e-9)(e+9)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(y-3)(y+3)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(s+4t)(s-4t)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(v+8)(v-8)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(y+5)(y-5)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(4p+7w)(4p-7w)</code></p>
<p>Expand the following.</p><p><code class='latex inline'>\displaystyle (3x - 1 + 2y + 1)(3x - 1 - 2y - 1) </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(r-8)(r+8)</code></p>
<p> Expand the following using <code class='latex inline'>(a - b)(a + b) = a^2 - b^2</code> short cut.</p><p><code class='latex inline'> \begin{array}{cccc} &(a) &(3x - 2)(3x + 2) & (b)& (5x + 1 )(5x - 1) & (c)& (\frac{x}{2} - \frac{1}{3})(\frac{x}{2} + \frac{1}{3}) \end{array} </code></p>
<p>Multiply.</p><p><code class='latex inline'>\displaystyle (7 a+10)(7 a-10) </code></p>
<p>Expand the following.</p><p><code class='latex inline'>\displaystyle (x - \frac{1}{x} + y + \frac{1}{y})( x - \frac{1}{x} - y - \frac{1}{y} ) </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(3x+4y)(3x-4y)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(q-6n)(q+6n)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(x+4)(x-4)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(x-9)(x+9)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(t-3)(t+3)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(z+6)(z-6)</code></p>
<p>Expand and simplify.</p><p> <code class='latex inline'>(x-7)(x+7)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(i-16)(i+16)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>\displaystyle (6k + 1)(6k -1) </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(u-5)(u+5)</code></p>
<p> Fully expand and collect the like terms using short cuts.</p><p><code class='latex inline'>\displaystyle (\sqrt{3y + x} + 1)(\sqrt{3y + x} - 1) </code></p>
<p> Fully expand and collect the like terms using short cuts.</p><p><code class='latex inline'>\displaystyle (x - y - 3)(x - y + 3) </code></p>
How did you do?
Found an error or missing video? We'll update it within the hour! ðŸ‘‰
Save videos to My Cheatsheet for later, for easy studying.